Pengaruh religiusitas dan dukungan sosial terhadap kualitas hidup penderita kanker serviks - Megawaty Megawaty (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2016)
The results showed that there was a significant effect of variables religiosity andsocial support on quality of life. The test results were minor hypothesis test thesignificance of each dimension of the independent variable on quality of life, thereare three significant regression coefficients, including experience, conviction andconsequences. The results showed the proportion of the variance of quality of lifefor all the independent variables explained 31.6% and 68.4% is influenced byother variables outside the research.